2020
DOI: 10.3389/fmed.2020.545813
|View full text |Cite
|
Sign up to set email alerts
|

Visual and Biochemical Evidence of Glycocalyx Disruption in Human Dengue Infection, and Association With Plasma Leakage Severity

Abstract: Background: Dengue is the most common arboviral infection globally; a minority of patients develop shock due to profound plasma leak through a disrupted endothelial barrier. Understanding of the pathophysiology underlying plasma leak is incomplete, but emerging evidence indicates a key role for degradation of the endothelial glycocalyx. Conclusions: We present the first human in vivo evidence of glycocalyx disruption in dengue, with worse visual glycocalyx damage and higher plasma degradation products associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 30 publications
3
21
1
Order By: Relevance
“…As yet details of the process by which this occurs remain obscure, in part due to difficulties in visualizing the structure of the EGL in vivo, but increased levels of several glycocalyx constituents have been documented, with some evidence indicating associations with the timing and severity of leakage (38)(39)(40), suggesting that structural characteristics of the EGL are altered during human DENV infections. In addition imaging studies of the sublingual microcirculation have shown an increase in the perfused boundary region within microvessels consistent with thinning of the EGL (41). In vitro and mouse model studies have demonstrated that dengue nonstructural protein 1 (NS1) can disrupt the surface glycocalyx both directly and/or through inflammatory-dependent pathways (42,43).…”
Section: Dengue Associated Vascular Leakage In the Context Of The Revmentioning
confidence: 98%
“…As yet details of the process by which this occurs remain obscure, in part due to difficulties in visualizing the structure of the EGL in vivo, but increased levels of several glycocalyx constituents have been documented, with some evidence indicating associations with the timing and severity of leakage (38)(39)(40), suggesting that structural characteristics of the EGL are altered during human DENV infections. In addition imaging studies of the sublingual microcirculation have shown an increase in the perfused boundary region within microvessels consistent with thinning of the EGL (41). In vitro and mouse model studies have demonstrated that dengue nonstructural protein 1 (NS1) can disrupt the surface glycocalyx both directly and/or through inflammatory-dependent pathways (42,43).…”
Section: Dengue Associated Vascular Leakage In the Context Of The Revmentioning
confidence: 98%
“…In addition, the software calculates the MVHS using the PBR-hf plus parameters representing the RBC filling and valid vessel density (the subset of vessels with enough red cells for tissue perfusion). Lower values of MVHS is suggested to reflect an overall worse microvascular health [18].…”
Section: Measurements Of Endothelial Glycocalyx Dimensionsmentioning
confidence: 98%
“…Higher PBR indicates thinner glycocalyx [22]. The software also enables assessment of the PBR estimated at a fixed high flow level (PBR-hf), which is suggested to be more accurate than measurements in capillaries without flow [18]. A higher PBR-hf reflects a more degraded glycocalyx.…”
Section: Measurements Of Endothelial Glycocalyx Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…One observational study based in Vietnam demonstrated that in patients with Dengue, SDF imaging demonstrated disruption to the glycocalyx, with worse observed glycocalyx injury and higher plasma concentrations of degradation products being associated with worse plasma leakage. The authors reported that in patients with dengue, the perfused boundary region (PBR hf), a surrogate for glycocalyx degradation, was higher in patients with Grade 2 vs. Grade 0 plasma leakage during the critical phase (PBR hf 1.96 vs. 1.36 µm for Grade 2 vs. Grade 0 plasma leakage on days 4-6, respectively, p < 0.001) (38). SDF, unfortunately, also has associated drawbacks including that it is prone to impaired visualization of capillaries, as well as interference of moving blood components, such as erythrocytes, with the quality of the image obtained (39).…”
Section: Studying the Endothelial Glycocalyx: Models And Imaging Techniquesmentioning
confidence: 99%